Health level of a mammal collection - Vania E. Rivera-León; Yolanda Hortelano-Moncada; Fernando A. Cervantes (Revista Mexicana de Biodiversidad)
The specimens deposited in a scientific collection are the physical evidence of living, as well as extinct, life forms. The physical state and the accuracy of the data and of the specimens stored in a collection may be assessed by the health level of the collection, which is represented by the collection profile and a health index. This paper presents a practical method for assessing a mammal collection health level. This method was designed and standardized following previous works and includes 8 levels. The method was applied to the Colección Nacional de Mamíferos (CNMA), housed at the Instituto de Biología, Universidad Nacional Autónoma de México, in 2011 and in 2015. The cataloged specimens were selected by a stratified random sampling in 2011 and a simple random sampling in 2015. Specimens that had not been cataloged were also assessed and selected by a stratified sampling in both years. A total of 336 specimens were evaluated in 2011 and 331 in 2015. The health index in the CNMA was 0.70 in 2015.